Epigenetic Memory and Control in Plants - Grafi, Gideon; Ohad, Nir.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Epigenetics commonly acts at the chromatin level modulating its structure and consequently its function in gene expression and as such plays a critical role in plant response to internal and external cues. This book highlights recent advances in our understanding of epigenetic mechanisms as a major determinant through which internal and external signals, such as those occurring during hybridization, flowering time, reproduction and response to stress, communicate with plant cells to bring about activation of multiple nuclear processes and consequently plant growth and development. The outcome of these processes may persist for generations long after the initial cues have expired and may contribute to plant evolution.
Plant Epigenetics: A Historical Perspective -- Environment-Induced Chromatin Reorganization and Plant Acclimation -- Epigenetic Regulation of Genome Stability in Plants in Response to Stress -- Epigenetic Control of Plant Immunity -- Epigenetic Control of Flowering Time -- Hormonal Signaling in Plants and Animals: An Epigenetics Viewpoint -- Epigenetic Signalling During the Life of Seeds -- Epigenetic Control of Cell Division -- Small RNA-Mediated Control of Development in Plants -- DNA Demethylation and Gene Imprinting in Flowering Plants -- Transgenerational Epigenetic Inheritance in Plants.
Keywords: Life sciences; Biochemistry; Plant breeding; Plant physiology; Life Sciences; Plant Genetics & Genomics; Plant Physiology; Plant Biochemistry